Analisis Rekonsiliasi Fiskal Laporan Keuangan PT.SFM Tahun 2020 Dalam Menghitung PPh Terutang - Purnamawati Helen Widjaja, Suryanti, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study was to analyze the fiscal reconciliation of PT. SFM financial statement by the applicable current taxation regulations. The research subject in this study is PT. SFM. The objects used are commercial financial statements 2020, corporate income tax, income tax art. 29, and corporate annual tax return 2020. The method used in this research is a descriptive method and the method of data collection is done through observation, documentation, and interviews with the company. The results of the study indicate that there are several mistakes in the fiscal reconciliation made by the company that is not in accordance with tax regulations, so it has an impact on the calculation of corporate income tax payable.